Global Tax Transparency and Fairness: Implications for Multinational Corporations in the Digital Economy - Loso Judijanto; Ahmed Al-Sabah; Ni Wayan Lia Apriani; Dod Setiawan Riatmaja (Yayasan Adra Karima Hubbi, 2025)
The expansion of the digital economy has intensified long-standing challenges in international taxation, particularly regarding tax transparency and fairness for multinational corporations operating across borders. Traditional tax frameworks struggle to address profit shifting and value creation driven by intangible assets and digital business models, prompting the development of global transparency initiatives. This study aims to examine the implications of global tax transparency and fairness frameworks for multinational corporations in the digital economy, with a focus on how enhanced disclosure affects corporate behavior and tax outcomes. A qualitative–comparative research design is employed, drawing on secondary data from international tax reports, corporate disclosures, and policy documents, complemented by sectoral comparison and an illustrative case study of a digital multinational corporation. The findings show that global transparency initiatives have increased reporting compliance and improved visibility of profit allocation and effective tax rates, particularly in high-income jurisdictions. However, significant disparities in tax outcomes persist across countries, driven by differences in regulatory capacity, enforcement strength, and the continued centrality of intangible assets in digital business models. The study concludes that tax transparency functions as a necessary but insufficient condition for achieving tax fairness in the digital economy. Its novelty lies in integrating tax justice and institutional legitimacy perspectives with empirical analysis of digital multinational corporations, highlighting the gap between formal transparency and substantive fairness and underscoring the need for coordinated reforms beyond disclosure requirements alone.